How Digital Services are changing the work dynamics in Community Health Centers or the Health Sector : A Comprehensive Review For Future Research agenda - Andrias Andrias; Setyo Riyanto; Dewi Nusraningrum; Muhammad Ali Iqbal (Jurnal Administrasi Bisnis, 2026)
The digital transformation in the healthcare sector, often referred to as the "virtual care revolution," has shifted the paradigm of healthcare delivery globally. Digital services such as telemedicine, health information systems, and mobile applications are no longer simply supporting infrastructure but have become strategic assets that are transforming the organizational structure and innovation models in primary healthcare facilities such as community health centers (Puskesmas). This study aims to synthesize existing literature through the Systematic Literature Review (SLR) method to explore how digital services change work dynamics in Community Health Centers or the health sector in general, both from a managerial and operational staff perspective. This SLR method was conducted by analyzing various case studies and quantitative and qualitative research related to the adoption of health technology in various countries. The analysis focused on changes in management competencies, staff work patterns, and the psychosocial impacts of the digital workplace. The findings of the review show that digital services change work dynamics in four main aspects , namely Managerial Competence, namely Health managers now play a vital role in designing, implementing, and guiding digital services, which requires informatics competencies and digital leadership beyond traditional clinical skills. Task - shifting is the implementation of digital platforms enabling substantial task shifting, where triage nurses and non-physician staff take on a greater role in initial consultations and patient management through algorithm support, significantly reducing the workload of general practitioners . Staff Performance and Well-Being: Effective use of information systems has been found to strengthen the relationship between work-life balance and healthcare worker performance by reducing administrative burdens and speeding up documentation . However, challenges such as “techno-stress” and blurred work boundaries have also emerged as new risks. Patient-Staff Interactions: Lack of digital literacy among vulnerable groups (such as the elderly) creates new work dynamics for healthcare staff who must provide additional support or training to patients to ensure effective use of technology. The conclusion is that digital services have fundamentally changed the dynamics of healthcare work, moving from a conventional clinic-centric model to a more efficient, data-driven, and patient-centered one. Long-term success requires a systematic approach that integrates staff digital skills training with robust organizational support policies .